Waiting Time Optimization with IP-Solver - Jaroslav Janacek; Michal Kohani (Communications - Scientific letters of the University of Zilina, 2010)
This paper deals with two different public transport problems, in which the same phenomenon of waiting time occurs. In the past, both the problems were solved in the same way, which included rearrangement of the original problems to simpler max-min problems. These simplified approaches were used due to that time state of optimization software. In connection with building new computational laboratories equipped with new optimization environment, we want to come back to the more precise original quadratic models of the problems and explore new possibilities in obtaining the optimal solution of the original problems. We have done an analysis of those quadratic programming problems, worked out a linearized model and completed the computational study to compare the max-min and quadratic approaches.